Test-retest reliability of muscular performance tests and compression garment interface pressure measurements: a comparison between consecutive and multiple day recovery - Brown, F.; Hill, M.; Renshaw, D.; Pedlar, C.; Hill, J.; Tallis, J. (Sports Engineering, 2023)
Whilst much research has been carried out on the use of compression garments for muscular recovery, reliability data on muscular performance and compression pressure measurements are lacking in non-resistance-trained populations. Therefore, the between-day and within-session reliability of garment interface pressure measurements and lower-limb maximal voluntary contraction forces was assessed in non-resistance-trained males and compared between groups testing on consecutive (CONSEC, n = 12), or non-consecutive days (= 48 h; REC, n = 12). Interface pressures were measured with a pneumatic sensor, before knee extension performance of the dominant leg (isometric, 60° s-1, 120° s-1 and 180° s-1) and 6 s cycle sprint performance were assessed. Peak isometric and isokinetic forces at 60° s-1 and 120° s-1 declined between days in CONSEC (p < 0.05; CV 5.1—6.6%), but not in REC (p > 0.05; CV 3.5-9.4%). Cycling peak power increased between days, regardless of group (p = 0.014; CV 4-4.8%). Interface pressures were similar between days and groups, but highly variable (p > 0.05; CV 6.8-17%). Familiarization with isometric and isokinetic testing may be unnecessary in non-resistance-trained males. Strength losses resulting from performance tests should be considered when assessing recovery on consecutive days. Conversely, 6 s sprint cycle testing required at least one familiarization session. Interface pressure measurements should be reported alongside reliability coefficients, while further research is needed to quantify the deterioration of interface pressures in relation to the reliability of these measurements when compression garments are worn for multiple days` recovery.